Adoption of Biotechnology in Livestock Production - Kimutai, Evans (International Journal of Livestock Policy, 2024)
Purpose: The general objective of this study was to investigate the adoption of biotechnology in livestock production. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the adoption of biotechnology in livestock production. Preliminary empirical review revealed that the adoption of biotechnology in livestock production offered significant benefits for productivity, animal health, and environmental sustainability. Genetic improvements, disease management, and reproductive technologies were highlighted as key areas where biotechnology had a positive impact. However, the study identified barriers such as high costs, regulatory challenges, and limited access in developing regions. Recommendations included supportive policies, increased investment in research, and capacity-building efforts to enhance the adoption of biotechnology, ultimately aiming to transform livestock systems and contribute to global food security and sustainable development Unique Contribution to Theory, Practice and Policy: The Theory of Planned Behaviour, Diffusion of Innovations Theory and Technology Acceptance Model may be used to anchor future studies on the adoption of biotechnology in livestock production. The study recommended integrating socio-economic factors into theoretical frameworks, enhancing practical training and capacity-building for farmers, and harmonizing regulatory frameworks to promote biotechnology adoption. It also emphasized public education campaigns to address misconceptions, suggested environmental sustainability practices, and called for ongoing research and innovation. These recommendations aimed to enhance productivity, sustainability, and resilience in the livestock sector, ultimately contributing to global food security and sustainable development.